Induction of differential T-helper-cell responses in mice infected with variants of the parasitic nematode Trichuris muris. - Bellaby, T (1996)
The resistance or susceptibility of mice to infection with the intestinal nematode parasite Trichuris muris is closely correlated with polarization of T helper (Th) cell responses to the type 2 (Th2) or type 1 (Th1) subset. Comparison of infections with three isolates of T. muris (E/K, E/N, and S) in three inbred strains of mice (CBA, C57BL/10, and B10.BR) has shown that host Th response phenotype can be parasite determined. Although the mouse strains used show genetically determined variation in ability to respond to T. muris (CBA > C57BL/10 > B10.BR), the speed of worm expulsion in a given strain depended upon the isolate used for infection (E/K > E/N > S). The two isolates that induced the most effective resistance (E/K and E/N) elicited parasite-specific host antibody responses that were dominated by immunoglobulin G1 (IgG1), and antigen-stimulated T cells from infected mice released interleukin-5 in vitro. With the isolate that induced the least host resistance (S), the dominant antibody response was IgG2a, and T cells released gamma interferon in vitro. These data show clearly that parasite variant-specific factors play a major role in Th subset polarization during infection.